The pinch-off effect and inhomogeneous barrier height analysis in Al/p-GaAs Schottky barrier diodes - Soylu, M.; Yakuphanoğlu, Fahrettin; Farooq, W. A. (Natl Inst Optoelectronics, 2011)
Al/p-GaAs Schottky barrier diodes (33 dots) were identically prepared. The effective barrier height values of one of the Al/p-GaAs Schottky barrier diodes were obtained as 0.681 and 0.945 eV from current voltage characteristics using the thermionic emission theory and capacitance voltage characteristics, respectively. The discrepancy between the barrier heights was explained in terms of barrier height inhomogeneity approach. It is seen that the Schottky barrier heights and ideality factors obtained from the I-V characteristics differ from diode to diode even if the samples are identically prepared. The origin of the barrier height inhomogeneity was analyzed by considering theoretical results obtained by Tung model. The obtained results indicate that the electron transport at the metal/semiconductor contacts are significantly affected by patches, but, the potential in front of small patches with low SBH surrounded by patches with high SBH is pinched off.
Keywords: GaAs; Schottky diode; I-V and C-V measurements; Barrier inhomogeneities